2015
DOI: 10.1111/tpj.12916
|View full text |Cite
|
Sign up to set email alerts
|

Guard cell photosynthesis is critical for stomatal turgor production, yet does not directly mediate CO2‐ and ABA‐induced stomatal closing

Abstract: SUMMARY Stomata mediate gas exchange between the inter-cellular spaces of leaves and the atmosphere. CO2 levels in leaves (Ci) are determined by respiration, photosynthesis, stomatal conductance and atmospheric [CO2]. [CO2] in leaves mediates stomatal movements. The role of guard-cell photosynthesis in stomatal conductance responses is a matter of debate, and genetic approaches are needed. We have generated transgenic Arabidopsis plants that are chlorophyll-deficient in guard cells only, expressing a constitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 87 publications
(132 reference statements)
2
54
0
Order By: Relevance
“…We can therefore only speculate on the reduced abundance of the BL receptors in the guard cells. In addition, it has been recently shown that guard cell photosynthesis (Azoulay-Shemer et al, 2015) and mobilization of starch in guard cells (Prasch et al, 2015;Horrer et al, 2016) are both central in stomatal turgor generation and opening. Inhibition of photosynthesis in the strong PR mutants, as indicated by reduced ETR (Figure 5A), is likely associated with reduced accumulation of starch in stomatal guard cells (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…We can therefore only speculate on the reduced abundance of the BL receptors in the guard cells. In addition, it has been recently shown that guard cell photosynthesis (Azoulay-Shemer et al, 2015) and mobilization of starch in guard cells (Prasch et al, 2015;Horrer et al, 2016) are both central in stomatal turgor generation and opening. Inhibition of photosynthesis in the strong PR mutants, as indicated by reduced ETR (Figure 5A), is likely associated with reduced accumulation of starch in stomatal guard cells (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Chloroplast reactions and a chloroplast HCO 3 2 -CO 2 sink may contribute to the CO 2 responses by enhancing the plasma membrane cellular influx of CO 2 -HCO 3 2 into guard cells, and additional research will be needed to investigate putative chloroplast contributions to the CO 2 response. Note that guard cell chloroplast functions during CO 2 control of stomatal movements may be independent of Rubisco (von Caemmerer et al, 2004) and are not dependent on guard cell photosynthesis (Azoulay-Shemer et al, 2015). Guard cell chloroplasts could function in malate-starch interconversion during stomatal movements (Outlaw and Manchester, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Guard cells are usually the only cells in the leaf epidermal layers that contain chloroplasts, but the photosynthetic capacity and physiological significance of guard cell chloroplasts have been a matter of debate for many years (Lawson et al, 2014). Guard cell-specific expression of chlorophyllase abolished the photosynthetic capacity of most guard cells but did not affect stomatal sensitivity to ABA or CO 2 stimuli (Azoulay-Shemer et al, 2015). However, guard cell turgor and energization were impaired, indicating that the photosynthetic capacity of guard cell chloroplasts is necessary for the guard cells to function properly.…”
Section: Tre6p and Regulation Of Stomatal Conductancementioning
confidence: 99%